Land for fish: Quantifying the connection between the aquaculture sector and agricultural markets - Tobias Heimann; Ruth Delzeit (Ecological Economics, 2024)
This study employs a global Computable General Equilibrium (CGE) model to quantify the effects of aquaculture production on agricultural markets, food prices and land use. We conduct a scenario analysis simulating, first, the fish sector developments expected by FAO; second, a rebuilding of sustainable wild fish stocks to achieve SDG 14; and third, a stronger expansion in aquaculture production with varying fishmeal supply. The results show direct effects of aquaculture production and limited fishmeal supply on agricultural production, land use, and food prices. Substituting fishmeal with plant-based feed when rebuilding sustainable fish stocks has lower effects on agricultural markets than growth in aquaculture production comparable to the first decade of this century. In addition, expanding aquaculture production increases prices for capture fish via fishmeal demand, instead of reducing capture fish prices by substituting consumer demand. Finally, rebuilding sustainable fish stocks has significant adverse effects on food prices in marine fish dependent regions in the southern hemisphere, and these regions need support in the transition period until sustainable fish stocks are achieved. The results of this study illustrate the interconnectedness of SDG 14 (life below water), SDG 15 (life on land) and SDG 2 (zero hunger).
Keywords: 330; Computable general equilibrium (CGE); Aquaculture; Land use; Agricultural markets; Agricultural commodity trade; SDGs; Fishmeal; Soymeal